(untitled) (Journal of the College of Basic Education, 2022)
The research study aimed at identifying the social benefits resulting For realizing this objective, a random sample was selected consisting of ( male students and teachers)to the college of dentistry . The functional descriptive approach was used because of its convenience for the nature of this study.. The findings were statistically analyzed, and the results indicated that the social benefits resulting from practicing physical activity are: social interaction,personal social benefits, social links cultural social benefit s and the belongings to the college , in this order which indicates the importance of the gradual practice of physical activity. The results indicated, also, the absence of statistical significant differences between the belongingness to the college and the social interaction, by students’ responses due to the gender variable, and statistical significant differences in the other domains, in favor of male students. Accordingly, the researchers recommended to increase the emphasis on extra-curricular physical activities at the college and encouraging the students and teachers to participate in such activities through the increase of activities, supervisors, trainers, halls and playgrounds for this purpose